ASSESSMENT OF RELIABILITY AND COMPARISON OF TWO ALGORITHMS FOR HAIL HAZARD DETECTION FROM AIRCRAFT - Braun, I.M.; Sinitsyn, R.B.; Yanovsky, F.J. (Proceedings of National Aviation University (archive), 2005)
This paper presents and analyzes two algorithms for the detection of hail zones in clouds and precipitation: parametric algorithm and adaptive non-parametric algorithm. Reliability of detection of radar signals from hailstones is investigated by statistical simulation with application of experimental researches as initial data. The results demonstrate the limits of both algorithms as well as higher viability of non-parametric algorithm. Polarimetric algorithms are useful for the implementation in ground-based and airborne weather radars.